PAMPs of Piscirickettsia salmonis Trigger the Transcription of Genes Involved in Nutritional Immunity in a Salmon Macrophage-Like Cell Line - Martínez, Danixa Pamela; Oliver, Cristian; Santibañez, Natacha; Coronado, José Leonardo; Oyarzún-Salazar, Ricardo; Enriquez, Ricardo; Vargas-Chacoff, Luis; Romero, Alex (Frontiers in Immunology, 2022)
The innate immune system can limit the growth of invading pathogens by depleting micronutrients at a cellular and tissue level. However, it is not known whether nutrient depletion mechanisms discriminate between living pathogens (which require nutrients) and pathogen-associated molecular patterns (PAMPs) (which do not). We stimulated SHK-1 cells with different PAMPs (outer membrane vesicles of Piscirickettsia salmonis “OMVs”, protein extract of P. salmonis “TP” and lipopolysaccharides of P. salmonis “LPS”) isolated from P. salmonis and evaluated transcriptional changes in nutritional immunity associated genes. Our experimental treatments were: Control (SHK-1 stimulated with bacterial culture medium), OMVs (SHK-1 stimulated with 1μg of outer membrane vesicles), TP (SHK-1 stimulated with 1μg of total protein extract) and LPS (SHK-1 stimulated with 1μg of lipopolysaccharides). Cells were sampled at 15-, 30-, 60- and 120-minutes post-stimulation. We detected increased transcription of zip8, zip14, irp1, irp2 and tfr1 in all three experimental conditions and increased transcription of dmt1 in cells stimulated with OMVs and TP, but not LPS. Additionally, we observed generally increased transcription of ireg-1, il-6, hamp, irp1, ft-h and ft-m in all three experimental conditions, but we also detected decreased transcription of these markers in cells stimulated with TP and LPS at specific time points. Our results demonstrate that SHK-1 cells stimulated with P. salmonis PAMPs increase transcription of markers involved in the transport, uptake, storage and regulation of micronutrients such as iron, manganese and zinc